(untitled) (Global Journal of Science Frontier Research, 2019)
The use of indicators provides several benefits among which the effective evaluation in the financing of agricultural loans to borrowers and also the support to the credit manager and portfolio in making strategic decisions. Despite the relevance of using metrics to aid in the financing of agricultural credit given the diversity of the existing business model, organizations have neglected their practice. Reasons for this fact include: (i) although access to credit is an significant factor in the adoption of agricultural technologies and increased agricultural incomes among rural farmers, are generally not sufficiently mature to make use of measurements or 2) researchers are not yet widely aware of the need for exploratory studies that identifies a mechanism to propose an agricultural credit financing strategy based on indicators through the analysis of a set of metrics. In this context, this article aims to conduct a systematic review to collect evidence on the existence of metrics and indicators that are specific for financing agricultural loans to rural families. The study produced 64 articles selected from the current literature and were not repeated because they were relevant.